The association of the MTHFR C677T polymorphism with inflammatory bowel diseases in the Israeli Jewish population: An example of genetic heterogeneity. Issue 51 (December 2016) - Karban, Amir; Feldman, Tzah; Waterman, Matti; Leiba, Ronit; Efrati, Edna
Abstract : Abstract: MTHFR C677T is a common gene polymorphism that has been shown to be associated with hyperhomocysteinemia. Studies on the role of MTHFR in inflammatory bowel diseases (IBD) have yielded conflicting results, perhaps due in part to genetic heterogeneity. The prevalence of the MTHFR C677T variant allele varies according to Jewish subpopulations: Ashkenazi vs non-Ashkenazi. The aim of this study was to examine the association between MTHFR C677T genotype and IBD in the different Jewish populations. DNA samples were assessed for the presence of the MTHFR C677T variant allele in 445 Jewish Israeli IBD patients: 338 with Crohn's disease [CD] (214 Ashkenazi and 124 non-Ashkenazi Jews) and 107 with ulcerative colitis [UC] (73 Ashkenazi and 34 non-Ashkenazi Jews), and in 347 healthy controls: 173 Ashkenazi and 174 Non-Ashkenazi Jews. Possible genotype–phenotype associations were investigated. We showed a significantly higher frequency of MTHFR 677T variant genotypes in non-Ashkenazi CD patients: Odds ratio of 1.86 for heterozygotes (CT) and 2.89 for homozygotes (TT) compared to non-Ashkenazi healthy controls. No significant association was found for UC in non-Ashkenazi patients or for CD or UC in Ashkenazi patients. Our findings suggest that the MTHFR 677T variant may contribute to the risk of CD in non-Ashkenazi but not Ashkenazi Jews. This may result from genetic heterogeneity and highlights the complexity of the genetic etiology of IBD.